2004
DOI: 10.1111/j.1460-9568.2004.03625.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of gabapentin and pregabalin on glutamate release at rat entorhinal synapses in vitro

Abstract: We have recently shown that the anticonvulsant drugs phenytoin, lamotrigine and sodium valproate all reduce the release of glutamate at synapses in the entorhinal cortex in vitro. In the present investigation we determined whether this property was shared by gabapentin and pregabalin, using whole-cell patch-clamp recordings of excitatory postsynaptic currents (EPSCs) in layer V neurons in slices of rat entorhinal cortex. Both drugs reduced the amplitude and increased the paired-pulse ratio of EPSCs evoked by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(118 citation statements)
references
References 61 publications
8
107
0
3
Order By: Relevance
“…The doses (10 -75 M) of gabapentin used in the present study are similar to those tested in other cellular studies such as in rat entorhinal slices (10 -100 M) (Cunningham et al, 2004;Brown and Randall, 2005) and rat trigeminal nucleus (30 M) (Maneuf et al, 2001). In contrast, low concentrations of gabapentin (Ͻ5 M) are effective in DRG (Yang et al, 2005) and high doses are required in cultured neurons (1000 M) (Cheng et al, 2006).…”
Section: Discussionsupporting
confidence: 71%
“…The doses (10 -75 M) of gabapentin used in the present study are similar to those tested in other cellular studies such as in rat entorhinal slices (10 -100 M) (Cunningham et al, 2004;Brown and Randall, 2005) and rat trigeminal nucleus (30 M) (Maneuf et al, 2001). In contrast, low concentrations of gabapentin (Ͻ5 M) are effective in DRG (Yang et al, 2005) and high doses are required in cultured neurons (1000 M) (Cheng et al, 2006).…”
Section: Discussionsupporting
confidence: 71%
“…31 It has been suggested that pregabalin may reduce the release of glutamate. 32 Therefore, blockade of the peripheral glutamate receptors by pregabalin in our current neuropathic pain model experiment may be another mechanism of action for reducing the allodynia.…”
Section: Discussionmentioning
confidence: 99%
“…100 -102 Other studies have shown inhibition of the release of glutamate and other neurotransmitters. [103][104][105] The variability in the effects on Ca 2ϩ current may relate to differences in expression of the ␣2-␦ subunit in different cell types or in response to different conditions. For example, in chronic neuropathic pain states, ␣2-␦ subunits may be upregulated, conferring gabapentin and pregabalin sensitivity.…”
Section: Voltage-gated Calcium Channelsmentioning
confidence: 99%